A digital design methodology for surgical planning and fabrication of customized mandible implants. Issue 1 (16th January 2017) - Abouel Nasr, Emad; Al-Ahmari, Abdurahman Mushabab; Moiduddin, Khaja; Al Kindi, Mohammed; Kamrani, Ali K.
Abstract : Purpose: The purpose of this paper is to demonstrate the route to digitize the customized mandible implants consisting of image acquisition, processing, implant design, fitting rehearsal and fabrication using fused deposition modeling and electron beam melting methodologies. Design/methodology/approach: Recent advances in the field of rapid prototyping, reverse engineering, medical imaging and image processing have led to new heights in the medical applications of additive manufacturing (AM). AM has gained a lot of attention and interest during recent years because of its high potential in medical fields. Findings: Produced mandible implants using casting, milling and machining are of standard sizes and shapes. As each person's physique and anatomical bone structure are unique, these commercially produced standard implants are manually bent before surgery using trial and error methodology to custom fit the patient's jaw. Any mismatch between the actual bone and the implant results in implant failure and psychological stress and pain to the patient. Originality/value: The novelty in this paper is the construction of the customized mandibular implant from the computed tomography (CT) scan which includes surface reconstruction, implant design with validation and simulation of the mechanical behavior of the design implant using finite element analysis (FEA). There has been few research studies on the design and customization of the implants before surgery, but there had been hardly any study related to customized design implant and evaluating the biomechanical response on the newly designed implant using FEA. Though few studies are related to FEA on the reconstruction plates, but their paper lacks the implant design model and the reconstruction model. In this research study, an integrated framework is developed for the implant design, right from the CT scan of the patient including the softwares involved through out in the study and then performing the biomechanical study on the customized design implant to prove that the designed implant can withstand the biting and loading conditions. The proposed research methodology which includes the interactions between medical practitioners and the implant design engineers can be incorporated to any other reconstruction bone surgeries.